Helping Behaviour and Knowledge Sharing Behaviour Moderated with Islamic Work Ethics among the Educational of Higher Institution - Salsabila Arum Pratiwi; Faraz Faraz (Personifikasi: Jurnal Ilmu Psikologi, 2023)
The psychological issue in knowledge management faced by many national and international institutions is on how to implement one of its elements, i.e. knowledge sharing behaviour in which it is not simple. This study aims to determine the direct correlation of helping behaviour and knowledge sharing behaviour and the indirect correlation of both variables mediated by Islamic work ethics. It involved the employees of private higher institutions in Yogyakarta with certain categories by using knowledge sharing behaviour scale from Yi, helping behaviour scale from Duang, Wong and Yue and Islamic work ethics scale from Ali and Al-Owaihan. The results of the direct analysis of helping behaviour and knowledge-sharing behaviour obtained the value of 0.001, meaning that they were positively related and very significant, but the F test results or their contribution only reached 13.2%. Meanwhile, the results of the indirect relationship analysis showed that the Islamic work ethic acted as a moderator with a significance value of 0.035 and an F-test result of 0.243 or 24.3%. It meant that, as a moderator, Islamic work ethics played a role in increasing the relationship between helping behaviour and knowledge sharing behaviour by 11.1%.